Two new species of Macrelmis Motschulsky (Coleoptera: Elmidae) and a new record of Macrelmis isis (Hinton) from Southeastern Brazil - Sampaio, Brunno Henrique Lanzellotti; Da Silva Dos Passos, Maria Inês; Ferreira- Jr., Nelson (Zootaxa, 2012)
Macrelmis is a genus distributed in the Palearctic, Nearctic and Neotropical regions. Currently there are 40 species, 20being recorded from Brazil but only two from Rio de Janeiro State. Herein two new species of Macrelmis are describedand figured: Macrelmis fluminensis sp. nov. and Macrelmis friburguensis sp. nov. A new record of Macrelmis isis from Rio de Janeiro State is given.